Analisis Perawatan Fasilitas Kendaraan di Unit Pertolongan Kecelakaan Penerbangan dan Pemadam Kebakaran (PKP-PK) Bandar Udara Internasional Juwata Tarakan - Al Fatah, Doni; Purnama, Yunus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Every airport operator is required to provide facilities that meet aviation safety and security requirements so that airport facilities can function properly, the operator is required to carry out maintenance within a certain period. Each airport is required to provide and provide PKP-PK services according to the airport category for PKP-PK required. The purpose of this research is to find out and analyze the causes of damage, find out how to maintain facilities, and find out the standard of vehicle eligibility at the PKP-PK unit of Juwata Tarakan International Airport. The research used a qualitative descriptive approach, the research was conducted in March 2023 by conducting structured interviews with 3 informants, namely the person in charge of the unit, senior and junior PKP-PK using a data validity test. Secondary data in the form of documents, books, journals and regulations as supporting and complementary data for writing this research. The obstacle faced by PKP-PK unit officers is that the vehicle is damaged on the engine part and there is no shop manual, this problem can be handled by optimizing maintenance. Treatment by officers refers to KP 04 of 2013. The vehicle eligibility standards in the PKP-PK unit are feasible to operate and meet the vehicle type standards starting from acceleration, beam distance, and top speed. Keywords: PKP-PK, Maintenance.